Pengaruh Budaya Organisasi, Patisipasi Anggota dan Komunikasi Terhadap Keberhasilan Koperasi Albasiko II di Pasaman Barat - Erman (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
This study aims to find: 1) the influence of organizational culture on the success of Cooperative Albasiko II in Pasaman Barat, 2) the effect of member participation on the success of Cooperative Albasiko II in Pasaman Barat, 3) the influence of communication on the success of Cooperative Albasiko II in Pasaman Barat 4) the influence of organizational culture, member participation and communication on the success of Cooperative Albasiko II in Pasaman Barat, The type of research conducted is Expost-Facto, The study population was 698 people from the Albasiko II Cooperative. The sample is 175 people. Primary data was collected through questionnaires using a Likert scale model that has been tested for validity and reliability. The data analysis technique used is Multiple Regression Analysis. The results of the study are: 1) There is a positive and significant influence of organizational culture on the success of Cooperative Albasiko II in Pasaman Barat, 2) There is a positive and significant influence of member participation on the success of Cooperative Albasiko II in Pasaman Barat, 3) There is a positive and significant influence of communication on the success of Cooperative Albasiko II in Pasaman Barat 4) There is a positive and significant influence of organizational culture, member participation and communication on the success of Cooperative Albasiko II in Pasaman Barat.The results of the analysis show that Indigo R2 (R-Square) is 0.759, this means that the influence of organizational culture, member participation and communication on the success of Cooperative Albasiko II in Pasaman Barat is 75.9% and the remaining 24.1% is influenced by variables others not included in the research model.